The Emerging Role of B Cells in the Pathogenesis of NAFLD. Issue 4 (18th June 2021) - Barrow, Fanta; Khan, Saad; Wang, Haiguang; Revelo, Xavier S.
Abstract : NAFLD is one of the leading causes of abnormal liver function worldwide. NAFLD refers to a group of liver conditions ranging from nonalcoholic fatty liver to NASH, which involves inflammation, hepatocellular damage, and fibrosis. Triggering of inflammation in NASH is a key event in the progression of the disease, and identifying the factors that initiate or dysregulate this process is needed to develop strategies for its prevention or treatment. B cells have been implicated in several autoimmune and inflammatory diseases. However, their role in the pathogenesis of NAFLD and NASH is less clear. This review discusses the emerging evidence implicating intrahepatic B cells in the progression of NAFLD. We highlight the potential mechanisms of B‐cell activation during NAFLD, such as increased hepatic expression of B‐cell–activating factor, augmented oxidative stress, and translocation of gut‐derived microbial products. We discuss the possible effector functions by which B cells promote NAFLD, including the production of proinflammatory cytokines and regulation of intrahepatic T cells and macrophages. Finally, we highlight the role of regulatory and IgA + B cells in the pathogenesis of NASH‐associated HCC. In this review, we make the case that future research is needed to investigate the potential of B‐cell–targeting strategies for the treatment of NAFLD.